2007
DOI: 10.1002/art.22941
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of cartilage destruction with intraarticular osteoclastogenesis inhibitory factor/osteoprotegerin in a murine model of osteoarthritis

Abstract: Objective. To investigate the effect of osteoclastogenesis inhibitory factor/osteoprotegerin (OPG) on chondrocytes in the development of osteoarthritis (OA) in vivo.Methods. To determine the role of endogenous OPG in the progression of OA, OA was surgically induced in OPG ؉/؊ mice and their wild-type (WT) littermates. To determine the role of exogenous OPG, knee joints of C57BL/6J mice with surgically induced OA were injected intraarticularly with recombinant human OPG (rHuOPG) or vehicle 5 times a week. All m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 36 publications
1
71
0
Order By: Relevance
“…Future therapeutic approaches could target reducing bone remodelling changes that take place in human OA subchondral bone, and data suggest that the modulation of OPG and RANKL could be an interesting target for such treatment. Since L-OA patients are in a remodelling/ resorptive phase, the inhibitory effect of OPG on bone resorption could therefore be proposed for this subpopulation; however, even though the administration of OPG in vivo in a murine OA model seems effective for the treatment of OA, 73 care should be taken since full-length OPG is known to be a survival factor for tumor cells. 9 1 Moreover, the anti-apoptotic effect of OPG via TRAIL can promote OA synovial membrane hyperplasia.…”
Section: Resultsmentioning
confidence: 99%
“…Future therapeutic approaches could target reducing bone remodelling changes that take place in human OA subchondral bone, and data suggest that the modulation of OPG and RANKL could be an interesting target for such treatment. Since L-OA patients are in a remodelling/ resorptive phase, the inhibitory effect of OPG on bone resorption could therefore be proposed for this subpopulation; however, even though the administration of OPG in vivo in a murine OA model seems effective for the treatment of OA, 73 care should be taken since full-length OPG is known to be a survival factor for tumor cells. 9 1 Moreover, the anti-apoptotic effect of OPG via TRAIL can promote OA synovial membrane hyperplasia.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study carried out in an experimental mouse model of OA revealed, upon OPG administration, reduced cartilage degradation through an effect on trabecular bone [123]. In the same line of thought, data from an OPG transgenic mouse model of OA suggested that the in vivo beneficial effect of the administration of OPG could be due to its capacity to bind tumour necrosis factor-related apoptosis-inducing ligand (TRAIL), an inducer of chondrocyte apoptosis [124]. However, data generated from an in vitro study in which treatment of human OA chondrocytes with OPG enhanced two catabolic factors involved in the pathophysiology of the disease [101] suggest that targeting the factor that mediates the effect of OPG, for example, by inhibiting RANKL, could lead to a new therapeutic approach against OA.…”
Section: Future Prospectsmentioning
confidence: 94%
“…The cartilage thickness was evaluated using Adobe Photoshop selection tools, which allowed us to select an area that spanned 450 m across the surface of the cartilage and extended down to the surface of the subchondral bone. The number of pixels within the area was converted to m 2 , and this converted value was divided by 450 m to estimate the mean cartilage thickness within the selected area (29,30).…”
Section: Methodsmentioning
confidence: 99%